2D van der Waals heterostructures of graphitic BCN as direct Z-scheme photocatalysts for overall water splitting: the role of polar π-conjugated moieties. Issue 41 (15th October 2020) - Wang, Zhijie; Luo, Zhibo; Li, Jia; Yang, Kang; Zhou, Gang
Abstract : A principle diagram of BC3 /C3 N and BC3 /BC6 N heterostructures immobilized by π–π stacking as direct Z-scheme photocatalysts for water splitting. Abstract : The application of two-dimensional (2D) graphitic carbon-based materials in photocatalysis has been limited to date, because the nature and role of π-conjugated moieties in them remain unclear. Herein we propose and study bilayer BC3 /C3 N and BC3 /BC6 N van der Waals heterostructures as direct Z-scheme photocatalysts for overall water splitting using density functional theory calculations. The roles of polar π-conjugated moieties in the formation, stacking configuration, and electronic and optical properties of bilayer van der Waals heterostructures are discussed. It is shown that polar π-conjugated moieties of graphitic BCN monolayers lead to a favorable π–π interaction, determining the most stable stacking configuration, and a long-range charge transfer between components. The former makes the electronic band structure of heterostructures favor photocatalytic water splitting in efficiency and energetics. The latter generates a built-in electric field for the interface recombination of photogenerated electron–hole pairs, indicating a Z-scheme mechanism. The delocalized nature of π-conjugated electrons in monolayer components allows for high carrier mobility of bilayer heterostructures, promoting the photocatalytic reactions on graphitic BCN monolayers. These findings show that 2D π-conjugated materials, including graphitic carbon-based materials and biological systems, have great potential in the design and development of 2D metal-free direct Z-scheme photocatalysts for environmental purification and energy conversion.